Ultra-precision machining of electroless nickel plated die materials - Pramanik, Alokesh; Soon, Neo; Rahman, Mustafizur (Bangladesh University of Engineering and Technology, 2002)
This paper deals with the effect of various cutting parameters on the cutting performance; specifically surface roughness and cutting forces, on electroless-nickel plated die using single point diamond tools. The four parameters under study include depth of cut, feed rate, spindle speed and phosphorus content. The experimental results showed that the cutting forces increase with the increase in the depth of cut, spindle speed and feed rate, and decrease with the increase of phosphorus content of the plating. The change of depth of cut shows no effect on surface roughness while surface roughness increases with the increase of feed rate and decreases with the increase of percentage of phosphorus content in the workpieces. In case of spindle speed, surface roughness decreases with the increase of spindle speed up to certain value then it starts to increase with the increase of spindle speed.